2005
DOI: 10.1002/cne.20572
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine-like immunoreactivity in the honey bee and cockroach: Comparable organization in the brain and subesophageal ganglion

Abstract: A serum raised against octopamine reveals in cockroaches and honey bees structurally comparable systems of perikarya and their extensive yet discrete systems of arborizations in neuropils. Numerous and prominent clusters of lateral cell bodies in the brain as well as many midline perikarya provide octopamine-like immunoreactive processes to circumscribed regions of the subesophageal ganglion, antennal lobe glomeruli, optic neuropils, and neuropils of the protocerebrum. There is dense octopaminergic innervation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
170
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(194 citation statements)
references
References 76 publications
21
170
1
2
Order By: Relevance
“…The axons of this neuron terminate extensively in the ALs, MB calyces and LPRs. In the cockroach, octopaminergic neurons with more or less similar morphology have been found (Sinakevitch, Niwa, & Strausfeld, 2005) and we speculate that some of these neurons convey sucrose US to various protocerebral areas. Roles of octopaminergic neurons for acquisition (Farooqui, Vaessin, & Smith, 2004;Nakatani, Matsumoto, Mori, Hirashima, Nishino, Arikawa, & Mizunami, 2009;Schroll, Riemensperger, Bucher, Ehmer, Voller, Erbguth, Gerber, Hendel, Nagel, Buchner, & Fiala, 2006;Schwaerzel et al, 2003;Unoki, Matsumoto, & Mizunami, 2005 In honey bees and fruit-flies, it has been suggested that both the MB and AL are the sites of association of olfactory CS and sucrose US for olfactory conditioning (Davis, 2005;Hammer & Menzel, 1998;Thum et al, 2007).…”
Section: Neural Pathways Mediating Conditioned Olfactory Responses Ofmentioning
confidence: 54%
“…The axons of this neuron terminate extensively in the ALs, MB calyces and LPRs. In the cockroach, octopaminergic neurons with more or less similar morphology have been found (Sinakevitch, Niwa, & Strausfeld, 2005) and we speculate that some of these neurons convey sucrose US to various protocerebral areas. Roles of octopaminergic neurons for acquisition (Farooqui, Vaessin, & Smith, 2004;Nakatani, Matsumoto, Mori, Hirashima, Nishino, Arikawa, & Mizunami, 2009;Schroll, Riemensperger, Bucher, Ehmer, Voller, Erbguth, Gerber, Hendel, Nagel, Buchner, & Fiala, 2006;Schwaerzel et al, 2003;Unoki, Matsumoto, & Mizunami, 2005 In honey bees and fruit-flies, it has been suggested that both the MB and AL are the sites of association of olfactory CS and sucrose US for olfactory conditioning (Davis, 2005;Hammer & Menzel, 1998;Thum et al, 2007).…”
Section: Neural Pathways Mediating Conditioned Olfactory Responses Ofmentioning
confidence: 54%
“…Although there are relatively few octopaminergic neurons in the honey bee brain, these neurons ramify extensively through regions of the insect brain known to be involved in reward learning (35). If this hypothesis is correct, it would suggest a framework for unifying the diverse roles of OA in the learning of rewarding stimuli (24), motivation to forage for floral rewards (36,37), arousal (19), and the evaluation of floral rewards communicated by dances (this work).…”
Section: Figmentioning
confidence: 91%
“…The distribution of octopaminergic neurons is well documented in insects including honeybees, fruit flies, blowflies, cockroaches, hawkmoths, and locusts. [105][106][107][108][109][110][111][112] The best characterized group of neuromodulatory neurons in insects constitutes a unique group of unpaired efferent median neurons, the somata of which are located at the dorsal/ventral midline of the subesophageal ganglion, thoracic, and abdominal ganglia; these neurons are known as dorsal unpaired median or ventral unpaired median neurons. [113][114][115][116] The classification of OCTlike immunoreactive neurons as clusters of cell bodies and perikarya within the cell body in the brain and the subesophageal ganglion has been reviewed elsewhere.…”
Section: Octopaminergic Neurons In the Insect Nervous Systemmentioning
confidence: 99%
“…[113][114][115][116] The classification of OCTlike immunoreactive neurons as clusters of cell bodies and perikarya within the cell body in the brain and the subesophageal ganglion has been reviewed elsewhere. 106,107,111,117 Most unpaired dorsal/ventral efferent median neurons are octopaminergic. 24,108,109 A subpopulation of the subesophageal ganglion dorsal/ventral unpaired median cells innervates most parts of the brain neuropils and is involved with specific activities and complex behaviors.…”
Section: Octopaminergic Neurons In the Insect Nervous Systemmentioning
confidence: 99%